A Rare Cause of Pulmonary Hypertension in a 4-Year-Old Toddler: Association of Cor Triatriatum Sinister and Pulmonary Arteriovenous Malformation - Can Yilmaz Yozgat; Erkan Cakir; Hakan Yazan; Hafize Otcu Temur; Kahraman Yakut; Yilmaz Yozgat (Case Reports in Pediatrics)
Cor triatriatum sinister is a rare congenital cardiac anomaly. The anomaly is caused by a fibromuscular membrane that divides the left atrium into two cavities. This membrane can lead to the obstruction of left atrial flow and also create pulmonary venous hypertension. Pulmonary arteriovenous malformation (PAVM) is notorious for its aberrant blood flow between the pulmonary arteries and veins. Herein, we report a case of a 4-year-old toddler who had a unique form of pulmonary hypertension presenting with cor triatriatum sinister and diffuse PAVM. After the surgical treatment of cor triatriatum sinister, both pulmonary arteriovenous malformation and pulmonary hypertension disappeared.